Features of the formation of agricultural land value in the European countries - Avramchuk, B. (Land Management, Cadastre and Land Monitoring, 2018)
The influence of the Common Agricultural Policy (CAP) on the agricultural sector of the European Union (EU) has been studied. The specifics of the formation and comparison of the calculated (by the method of capitalization of net operating or rent income) and the market value of agricultural land in Europe and the Netherlands, in particular, are justified. Keywords: agricultural land, value, the land market, the European Union, the Common Agricultural Policy.